Effect of Turbulent Fluctuations on Neutral Particle Penetration and Charge Exchange Sputtering. Issue 4 (June 2014) - Mekkaoui, A.; Kotov, V.; Reiter, D.; Boerner, P.
Abstract In this contribution we present results on the effect of turbulent plasma fluctuations on the transport of atoms and molecules as well as on impurities sputtered due to charge exchange atomic bombardment. These phenomena are investigated using the kinetic Monte‐Carlo particle transport code EIRENE and a statistical model of plasma fluctuations. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)